UJI PENGGUNAAN BEBERAPA JENIS ABU TERHADAP PERTUMBUHAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Rachmad Ryadi; Sampoerno '; Al Ikhsan Amri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Plant oil palm (Elaeis guineensis Jacq.) is one of plantation crop which plays an important role for Indonesia as a mainstay commodity for export and commodity that can increase farmers’ income results. Nurseries is the initial activity in the field that aims to prepare seedlings ready for planting. The research aims to determine the effect of some types ash on the growth of oil palm seedlings and determine the type of ash is best for growth of oil palm seedlings in the main nursery. Experimental research conducted at the Faculty of Agriculture University of Riau, from April to August 2015. This study uses a Completely Randomized Design (CRD) which consist of 6 treatments and 4 repeat, to obtain 24 units of trial. Treatment given, among others : without dust, ash oil palm empty bunch, ash of oil palm fruit shells, ash sawdust, ash rice husk and ash rice straw. Data were analyzed using ANOVA and continued with further test Duncan’s New Multiple Range Test (DNMRT) at 5%. Research that has been carried out showed that giving some kind of as in oil palm seedlings show the real effect of the parameters on the increase in diameter hump and dry weight of seedlings, but the effect not real of the parameters as heigh of seedlings, increase the number of leave, root volume and ratio crown roots. Treatments sawdust ash and ash oil palm empty bunch showed better results for the growth of iol palm seedlings. Keywords: Ash, oil palm, main nursery